Impact of extreme environmental conditions: Foraging behaviour and trophic ecology responses of a diving seabird, the common diving petrel. (November 2021) - Fromant, Aymeric; Delord, Karine; Bost, Charles-André; Eizenberg, Yonina H.; Botha, Jonathan A.; Cherel, Yves; Bustamante, Paco; Gardner, Brett R.; Brault-Favrou, Maud; Lec'hvien, Arnaud; Arnould, John P.Y.
Graphical abstract: Highlights: Successive summer marine heatwave events in south-eastern Australia. Bottom-up effect inducing major impact on the breeding and foraging ecology of a zooplanctivorous seabird. Common diving petrels exhibited abnormally low breeding success, increased foraging effort and shifted to lower quality prey following marine heatwave events. Results indicate the relevance of such species to monitor the effects of changing oceanographic conditions. Abstract: The reproductive success of birds is strongly driven by environmental conditions at different time scales. Thus, during periods of low food availability, breeding success is constrained by the ability of adults to adapt their foraging effort and feeding behaviour to maintain regular incubation shifts and chick provisioning. However, while large seabirds can buffer disruptions in prey availability, the ecophysiological constraints of smaller species may limit their behavioural flexibility. By combining information on at-sea movements, foraging habitat, trophic niche, and breeding success, this study evaluated the effects of intense variability in oceanographic conditions on common diving petrels ( Pelecanoides urinatrix ) at the northern extent of their range in south-eastern Australia during four consecutive breeding seasons. Unusually low breeding success (6 and 0%) was observed during two years with intense heatwave events, which were associated with higher foraging effort (foraging trips twice longer) and a substantial shift in trophic niche (lower blood δ 15 N values). These findings suggest that common diving petrels in Bass Strait may have reached a critical threshold above which buffering the effects of environmental variability on their reproductive output is not possible. The clear cascading impacts that marine heatwaves have on zooplankton feeders illustrate the profound bottom-up effect induced by such extreme environmental variations, and suggest strong impact on higher-trophic levels. The wide, circumpolar breeding distribution of the common diving petrel, and its high sensitivity to variations in oceanographic conditions, suggest that this species may be a suitable model to study short-term and long-term behavioural responses to the effects of climate change throughout the Southern Ocean.